The effect of spectral splatter in determining hearing threshold using tone burst Auditory Brainstem Response (ABR) in clinical setting - Saad, Amirul Asraf Md (Universiti Sains Malaysia, 2012)
A prospective study to reveal the effect of spectral splatter in determining hearing threshold using tone burst Auditory Brainstem Response (ABR) in clinical setting. Ten subjects were participated in this study with total of twenty ears (right and left). Five subjects were male and five subjects were female. Subjects were 100% Malay adults. Subjects were recruited among students of University of Science Malaysia from April to May 2012. Test was done by changing the cycle of tone burst ABR, varying with 2- 1-2, 1-1-1, and 0.5-1-0.5 cycle of rise-plateau-fall time during testing on subject with artificial hearing loss. Result shows significant difference of hearing threshold between 2-1-1, 1-1-1 and 0.5-1-0.5 of rise-plateau-fall time of tone burst ABR. The result’s correlation of all three cycle was not differ much with Pure Tone Audiometry (PTA)